The Influence of the Marketing Mix on Customer Satisfation - Dyah Murdayani Kusumaningrum; Martaleni (Journal of Management Research and Studies, 2023)
This study aims to examine and analyze the effect of the marketing mix on customer satisfaction at the Nelongso Pakis Fried Chicken restaurant, Malang Regency. The population in this study were all customers who had visited the Nelongso Pakis Fried Chicken restaurant. The research method used is a quantitative method. Samples were taken as many as 240 respondents using purposive sampling technique. The type of data used in this research is primary data. Data collection techniques using a questionnaire. Hypothesis testing uses multiple linear regression analysis techniques with SPSS version 21.0. Based on the results of the partial analysis (T test) shows that the variable product, price, promotion, and people have a significant effect on customer satisfaction. While the place, process, and physical evidence variables have no significant effect on customer satisfaction. Furthermore, the results of the simultaneous analysis (Test F) showed that all independent variables had an effect on customer satisfaction at the Nelongso Pakis Fried Chicken Restaurant, Malang Regency.